Unhealthy alcohol use is associated with postoperative complications in veterans undergoing lung resection - Graf, Solomon A. (J Thorac Dis, 2018)
BACKGROUND: Lung resections carry a significant risk of complications necessitating the characterization of peri-operative risk factors. Unhealthy alcohol use represents one potentially modifiable factor. In this retrospective cohort study, the largest to date of lung resections in the Veterans Health Administration (VHA), we examined the association between unhealthy alcohol use and postoperative complications and mortality. METHODS: Veterans Affairs Surgical Quality Improvement Program data recorded at 86 medical centers between 2007 and 2011 were used to identify 4,715 patients that underwent lung resection. Logistic regression models, adjusted for demographics and comorbidities, were fit to assess the association between unhealthy alcohol use (report of >2 drinks per day in the 2 weeks preceding surgery) and 30-day outcomes. RESULTS: Among 4,715 patients that underwent pulmonary resection, 630 (13.4%) reported unhealthy alcohol use (>2 drinks/day). Overall, postoperative complications occurred in 896 (19.0%) patients, including pneumonia in 524 (11.1%). The rate of mortality was 2.6%. In adjusted analyses, complications were significantly more common among patients with unhealthy alcohol use [odds ratio (OR), 1.42; 95% confidence interval (CI), 1.15–1.74] including, specifically, pneumonia (OR, 1.69; 95% CI, 1.32–2.15). No statistically significant association was identified between unhealthy alcohol use and mortality (OR, 1.27; 95% CI, 0.75–2.02). In secondary analyses that stratified by smoking status at the time of surgery, drinking more than 2 drinks per day was associated with post-operative complications in patients reporting current smoking (OR, 1.51; 95% CI, 1.18–1.91) and was not identified in those reporting no current smoking at the time of surgery (OR, 1.23; 95% CI, 0.79–1.85). CONCLUSIONS: In this large VHA study, 13% of patients undergoing lung resection reported drinking more than 2 drinks per day in the preoperative period, which was associated with increased risk of post-operative complications. Unhealthy alcohol use may be an important target for perioperative risk-mitigation interventions, particularly in patients who report current smoking.